2017
DOI: 10.14687/jhs.v14i4.4948
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral care provided with three different tools in patients receiving mechanical ventilation<p>Mekanik ventilatöre bağlı hastalarda üç farklı araçla verilen ağız bakımının etkisi

Abstract: Aim: This study was conducted to investigate the effects of oral care provided suction toothbrush, suction sponge stick and sponge stick in patients receiving mechanical ventilation. Material and method:The study was conducted as a quasi-experimental study. Thirty patients who were over 18 years of age and receiving mechanical ventilation comprised the study sample. The patients who met the inclusion criteria were divided into three groups: the suction toothbrush group, the suction sponge stick group and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…In the study by Ozveren, it was indicated that vacuum toothbrush was more effective in oral care and it had an improving effect on oral health. [4] In the study by Marino et al, it was reported that there were significant reductions in gingival index and dental plaques among the patients who were given oral care by toothbrushes. [18] Electrical toothbrushes were found to be more effective than manual toothbrushes in removing plaques and preventing gingivitis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In the study by Ozveren, it was indicated that vacuum toothbrush was more effective in oral care and it had an improving effect on oral health. [4] In the study by Marino et al, it was reported that there were significant reductions in gingival index and dental plaques among the patients who were given oral care by toothbrushes. [18] Electrical toothbrushes were found to be more effective than manual toothbrushes in removing plaques and preventing gingivitis.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, presence of endotracheal tube, presence of pressure on the mucosa, permanent opening of the mouth and adhesive bands or bandages used for the detection of endotracheal tube may cause a disturbance in the integrity of mouth and surrounding tissues. [2][3][4] When sufficient oral hygiene could not be provided in the intensive care patients who could not meet individuals needs independently and who were followed up mostly under sedation, oral problems such as bad breath, alterations in the sense of taste, gingivitis, mouth dryness, lip cracks, stomatitis and mouth ulcers have been observed. [5] Moreover, entry of the bacteria into respiratory tract is facilitated in these patients due to endotracheal tube; and secretion is increased by accompanying disturbance in coughing reflex.…”
mentioning
confidence: 99%
See 2 more Smart Citations